Mechanics for materials and technologies - Altenbach, Holm, 1956-; Goldstein, R. V.; Murashkin, Evgenii (Advanced structured materials ;, 2017)
This book shows impressively how complex mathematical modeling of materials can be applied to technological problems. Top-class researchers present the theoretical approaches in modern mechanics and apply them to real-world problems in solid mechanics, creep, plasticity, fracture, impact, and friction. They show how they can be applied to technological challenges in various fields like aerospace technology, biological sciences and modern engineering materials.